Theoretical framework of the Preliminary Title in the Peruvian Civil Code: A comparative law approach - Varsi Rospigliosi, Enrique Antonio (2024)
The Preliminary Title of Civil Codes is a cornerstone in comparative law, as it provides essential guidelines for the interpretation and application of legal norms. Although its classical regulation has demonstrated a degree of effectiveness in addressing new legal, economic, and technological realities, it remains crucial for maintaining the coherence of the legal system. This article aims to propose a comprehensive theoretical framework for analyzing the Preliminary Title of the Peruvian Civil Code, addressing a gap identified in national legal doctrine and highlighting its structural and normative role within the legal system by establishing the guiding principles for interpreting and applying civil law. Through a detailed analysis and a comparative approach, the article underscores the importance of the Preliminary Title in preventing and resolving social conflicts, promoting justice, and upholding the rule of law. In summary, it emphasizes its role as a pillar for regulating private and public relationships and its influence across the entire legal system, reaffirming its constitutional vocation.